1995
DOI: 10.1002/j.2048-7940.1995.tb01616.x
|View full text |Cite
|
Sign up to set email alerts
|

Wives’ Reported Role Changes Following a Husband's Stroke: A Pilot Study

Abstract: The purpose of this pilot study was to look at changes in the roles of wives when their spouses became disabled due to a stroke. Data collection tools included Buxbaum's Marital Role Questionnaire, which was administered first in the rehabilitation hospital and again at home 2 weeks after the spouses' discharge. Ten subjects participated in this study. Results suggest that (a) wives' responsibilities increased significantly after the husband's stroke, (b) wives' satisfaction with household responsibilities dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…The perceived impact of caring on the extended family was referred to by all the participants, and this contributes to an identified gap in knowledge [32] by demonstrating that impact on family roles is an issue for younger carers as well as older carers [15,22]. The need to re-define and re-negotiate the caring roles of family members was perceived as a source of pressure on relationships, and resonates with studies demonstrating that stroke produces a period of role destabilisation and disequilibrium [17].…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…The perceived impact of caring on the extended family was referred to by all the participants, and this contributes to an identified gap in knowledge [32] by demonstrating that impact on family roles is an issue for younger carers as well as older carers [15,22]. The need to re-define and re-negotiate the caring roles of family members was perceived as a source of pressure on relationships, and resonates with studies demonstrating that stroke produces a period of role destabilisation and disequilibrium [17].…”
Section: Discussionsupporting
confidence: 54%
“…In common with previous research, these partners of young stroke survivors perceived major changes in most areas of their life; restriction of social life, the need to take on roles and tasks previously performed by the stroke survivor, changes in employment and changes in relationships [3,12,16,17,22]. Although the life satisfaction of carers of young stroke survivors is known to decrease for up to 1 year after stroke [29], and the quality of life of carers of mixed age is similarly reduced [9], the current study demonstrates that re-appraisal, re-adjustment and acceptance of changed lives may occur at a later stage and contribute to positive psychological adjustment.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Changes to estabUshed pattems of daily Ufe can represent a major strain for carers (Periard and Ames, 1993). QuaUtative American studies of the effects of stroke on wives of stroke patients have demonstrated the unfamUiar new responsibUities of role changes, m addition to caring for the stroke patient (Rosenthal et al, 1993;Enterlante and Keme, 1995;Robinson-Smith and Mahoney, 1995).…”
Section: Adjustmentmentioning
confidence: 99%